India and China economic initiatives: potential areas for cooperation and the impacts on South Asia region / Muhammad Aiman Nasuha Azari - Azari, Muhammad Aiman Nasuha (2019)
The title “Giant of Asia” will always remind the world on two Asia’s countries which are India and China. These two countries with great history and civilizations since thousands years ago become their source of pride in this modern era. Regardless of this matter, India and China can’t avoid from having dispute in terms of politics and territories with each other. The Sino-Indian War in 1962 was among the evidences that clearly showed how bad the relationship between these two countries. The rise of India and China in terms of economic had opened up numerous windows of opportunities for cooperation. For that reason, by having an analysis on the economic cooperation between India and China, the potentials areas in economic areas for their cooperation can be identified. Besides that, the impacts from their economic initiatives towards South Asia region also can be identified. There are two main objectives of this study. First of all is to identify the potential areas of cooperation between India and China in economic sector that can be achieved. Next is to investigate the impacts of India and China economic initiatives towards the South Asia region. This study based on the content analysis from information in articles, reports and document from numerous resources. Besides that, the findings in this study also being obtained from interview with academicians and experts in this field. From this study, it can be found that manufacturing and Information Technology (IT) sector are the most potential economic area that can be closely cooperates between India and China. The economic initiatives by these countries also bring numerous opportunities for South Asia’s countries such as Pakistan, Bangladesh, Bhutan, Nepal, Sri Lanka, Maldives, and Afghanistan and last but not least India itself to chip in.